Evaluation Of Land Capabilities For Coffee And Durian Crops To Sustainable Agriculture - Muara Dhika; Rahastri Rengganis Sukma; Avianita Agustiani; Damasa Ines Larrisa; Maroeto Maroeto (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The utilization of land that is not corresponding to its capabilities will accelerate land degradation. Therefore, in this study, the land capability was assessed to determine land capability classes and land use directions for applying sustainable agricultural systems in coffee and durian cultivation areas in the Wonosalam region, Jombang, East Java. The procedures included field observations, soil sampling, and laboratory analysis. Soil samples were taken at two depths, 0-30 cm and 30-60 cm, carried out by taking samples at two different points, then analyzed in a composite manner. The results showed that the class of land capability for planting coffee and durian was in class VII, which had a limiting factor in the form of slopes. Limited grazing and nature reserves are the focus of class VII land-use guidelines so that the land use direction follows the characteristics of the nature reserve and the principles of sustainable agriculture. Concerning long-term agriculture, we need to use conservation strategies both vegetatively and mechanically. Thus, the land that is the research site will be able to maintain its carrying capacity and minimize the decline in land quality and quantity on land use in the Wonosalam, Jombang area.